Exploring The Function and Philosophy of The Mbaru Gendang: The Cultural House of Manggarai, Flores, NTT - Ampur, Afrianus; Maku, Hendrikus; Edu, Ambros Leonangung; Firmanto, Antonius Denny; Nanto, Yohanes De Brito (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Indonesia has thousands of local wisdom. One of them is the Mbaru Gendang. Mbaru Gendang is the cultural house of the Manggarai community. The Mbaru Gendang has a beautiful Indonesian philosophy. Therefore, the focus of this paper is to explore the philosophy of the Mbaru Gendang as a characteristic and purpose of life for the Manggarai Community. This paper aims to explore the philosophy of the symbols, functions and forms of the Mbaru Gendang. The author uses the method of observation and literature study. This study found that the shape and symbol of the Mbaru Gendang hold very strong cultural and philosophical values. This paper contributes to the high philosophical values in the Mbaru Gendang as a reference and purpose of life for the Manggarai people. In addition, this paper is an attempt to explore the Mbaru Gendang as a characteristic and main value of Manggarai culture.